Caregiver acceptance of a patient navigation program to increase human papillomavirus vaccination in pediatric clinics: a qualitative program evaluation - Jacqueline M. Hirth; Abbey B. Berenson; Leslie E. Cofie; Lena Matsushita; Yong-Fang Kuo; Richard E. Rupp (Taylor & Francis Group, 2019)
Objective: The purpose of this evaluation was to examine the acceptability of a multi-component patient navigator (PN) intervention program designed to decrease barriers to human papillomavirus (HPV) vaccination among caregivers of adolescents. We sought to understand the most important components of the program from the caregivers' perspective and to evaluate remaining barriers to vaccination. Method: Caregivers of children 9-17 years old (N = 102) participated in qualitative semi-structured interviews with questions informed by the Theory of Planned Behavior. These interviews assessed experiences with a PN program which offered HPV vaccination, scheduling, and reminders in pediatric clinics. We included randomly selected 46 program participant transcripts and 11 decliner transcripts. A thematic approach was used to analyze transcripts for themes related to acceptability of HPV vaccination, important program components, and any problems encountered. Results: Major themes included: reasons for making HPV vaccination decision, helpful program components and suggestions for improvement, and remaining barriers to vaccination. Those who declined vaccination stated that their child was too young or not ready to think about sex, or they did not have enough information to make a decision. However, they felt that PNs were respectful of their decision. Program participants felt that vaccination was an important way to prevent cancer. Program participants had often not been aware of the vaccine and felt that having it explained was very helpful. Conclusion: This program evaluation found that caregivers of pediatric patients, even those who declined the HPV vaccine, appreciated the program and felt it provided important information about the vaccine.